2023
DOI: 10.2147/ijn.s375918
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization with Gadolinium Chelate-Coated Gold Nanoparticles Prevents Aggressiveness and Invasiveness in Glioblastoma

Abstract: Purpose This study aimed to evaluate the radiosensitizing potential of Au@DTDTPA(Gd) nanoparticles when combined with conventional external X-ray irradiation (RT) to treat GBM. Methods Complementary biological models based on U87 spheroids including conventional 3D invasion assay, organotypic brain slice cultures, chronic cranial window model were implemented to investigate the impact of RT treatments (10 Gy single dose; 5×2 Gy or 2×5 Gy) combined with Au@DTDTPA(Gd) nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Gold particles can be associated with carrier molecules because of their high affinity. Simultaneously, gadolinium particles have the advantage of being able to be chelating agents for molecular imaging in nuclear medicine [ 84 ]. In addition to DNA breaks, the biological effects discovered are membrane alterations and functions on the cell cycle, mitochondria and tumor vascularization.…”
Section: Radiation-sensitizing Nanoparticlesmentioning
confidence: 99%
“…Gold particles can be associated with carrier molecules because of their high affinity. Simultaneously, gadolinium particles have the advantage of being able to be chelating agents for molecular imaging in nuclear medicine [ 84 ]. In addition to DNA breaks, the biological effects discovered are membrane alterations and functions on the cell cycle, mitochondria and tumor vascularization.…”
Section: Radiation-sensitizing Nanoparticlesmentioning
confidence: 99%
“…The investigation into the combination of cell therapy and nanotechnology found that gadolinium-neutron capture therapy (Gd-NCT) can be used for glioblastoma multiforme (GBM) treatment [56]. More recent evidence [57] highlights that the Au@DTDTPA(Gd) NPs, in combination with conventional external X-ray irradiation, may be used as a radio-sensitizer for GBM treatment.…”
Section: Gadolinium-based Nanoparticlesmentioning
confidence: 99%
“…Furthermore, gold nanoparticles alone have been shown to localize within human glioblastoma cell lines and promote the radiosensitization of sensitive and resistant cells [ 72 ]. Chelated gold and gadolinium nanoparticles were also recently shown to cause radiosensitization of in vitro human glioblastoma cells and diminish their ability to invade surrounding brain parenchyma [ 73 ].…”
Section: Theranosticsmentioning
confidence: 99%